The determination of economic and public health benefits achievable by increasing regular physical exercise - Ács, Pongrác; Stocker, Miklós; Oláh, András (Applied Studies in Agribusiness and Commerce, 2013)
There are various methods at our disposal to determine the direct expenses of the factors, which influence the state of health – such as inactive lifestyle –, but research studies aimed at comprehensively determining all direct and indirect expenses have not been conducted in Hungary, yet. We desired to remedy this deficiency with our research, which was prepared at the commissioned order and with the support of the Hungarian Society of Sport Science and the Department for Sport of the Ministry of Human Resources of the Hungarian Government. Using the factual data of OEP (National Health Insurance Fund) we determined the annual cost of illnesses, along with the extent of the cost of physical inactivity, (HUF billion), and we prepared an estimate of the possible amount of savings in Hungary (sick-pay, medication costs etc.), the methodology of which we adapted from international research projects, thus the resulting data in the case of Hungary will later be comparable to international data. International examples reveal the savings achievable by increasing physical exercise in a broad range, even though having conducted the research in different ways and time periods. All research projects concur about one thing, namely that the reduction of physical inactivity can result in significant savings. Our results have verified this statement statistically as well.